Rising Incidents of Smuggling of Illegal Workers from Indonesia (Case of Illegal Workers from East Nusa Tenggara) - Nasywa Laffaiza (CV. Rayyan Dwi Bharata, 2023)
The problem of illegal labor smuggling is a serious problem. There are many things that must be reconsidered when a prospective worker wants to become a migrant worker. So that the presence of this research is to find out legal issues related to workers with illegal status which are balanced with workers with legal status as a form of comparison. This research was conducted using a method to facilitate and be able to support research interests. Where this research uses normative legal research. With this form of study using the statutory method, it is descriptive and analytical in nature and examines the meaning and intent of several sources of statutory regulations as well as the rules and standards used. By using secondary legal materials taken from several literacies such as journal articles and the thoughts of scholars as a basis for research and consideration in the analysis carried out by researchers. The method used for data collection in this study was library research, namely examining related library materials when conducting research. The results of the analysis stated that the lack of education and outreach related to legal and illegal status to the community was considered lacking. In addition, there is a lack of explanation why the process of obtaining legal status takes longer than that of workers with illegal status.